Effects of Cigarette Smoking on Quadriceps Tendon Stiffness using Ultrasound Elastography - Al-Qahtani, Mahdi; Fakhouri, Abdulaziz S.; Javed, Ravish (British Journal of Healthcare and Medical Research, 2023)
The present study aimed to find Quadriceps Tendon (QT) stiffness variation due to cigarette smoking by using Ultrasound Elastography (UE). The UE depicts the tendon stiffness in terms of Strain Ratio (SR). Mature and healthy individuals were incorporated in the present study. Strict exclusion criteria were followed. Nine individuals were recruited in the present study out of which seven were non-smokers or control group and two were smokers. Each subject’s QT stiffness was measured using the UE technique. All participants had the right side of their body as their dominant side. The mean age was 20.9 ± 1.3 years, height was 177.3 ± 6.0 centimeters, weight was 76.3 ± 9.5 kilograms and BMI was 24.3 ± 3.0. Presence of statistically significant difference in SR values was present between non-smokers and smokers. Moreover, difference in QT length and thickness values was also present. The present study revealed that the QT stiffness was statistically significantly higher among smokers in comparison to non-smokers, whereas QT length and thickness were lesser in smokers when compared with non-smokers. Therefore, from the present study it is apparent that cigarette smoking effects quadriceps tendon stiffness, length and thickness.